Criminal Responsibility For The Occurring of a Patient Safety Incident In a Health Center Which Results in the Leaving of A Baby's Head in a Mother's Womb Before Birth in the Perspective of Health Law in Indonesia - Yandriza; Lucky Raspati; Siska Elvandari; Anggun Irwan Nanda (Master of Law Program, Ekasakti University, 2024)
This research was motivated by a mother from Panpajung Village, Modung, Bangkalan, Madura, East Java, reporting a midwife to the police on suspicion of malpractice. The mother lost the baby she was carrying after the baby's head was left in the womb during the birth process at the health center. The explanation of this case is interesting for the author to discuss who should be responsible for it all, and what criminal responsibility is like regarding the occurrence of patient safety incidents at a community health center resulting in the baby's head being left in the mother's womb before birth in the perspective of health law in Indonesia. The death that occurred to the baby is of course the subject of our collective evaluation, while remaining in favor of the aim of criminal law to provide protection against crimes against a person's body and life, and the death that occurred to the baby, of course, is contrary to the mandate of Law no. 39 of 1999 concerning Human Rights regarding: The Right to Life, and the Right to Defend Life, and also contradicts the aim of health law to reduce suffering, prolong life, and accompany patients until the end of their lives.